Measuring and maintaining acceleration records obtained from 3D MEMS - Ravali, K.; ASR.Murty, Dr.; Pavani, V.; Prathyusha, B. (International Journal of Engineering and Technology, 2018)
Tracing or tracking of an object or a link is needed in many engineering applications. Achieving it in real time applications using MEMS or the traditional accelerometers is also a well-known method. Measuring acceleration in [3] directions is needed in handling equipment, material transfer and in manufacturing industry.In this work, Calibration of accelerometer sensor ADXL335 is carried out first to show the accurate values of â€žgâ€Ÿ. Then, the measurement of acceleration is carried out as per the code written in Arduino IDE. ADXL335 is interfaced with NODE MCU. NODE MCU uses HTTP protocol to send the measured acceleration values to cloud platform. ThingSpeak is the cloud platform chosen for this purpose. ThingSpeak requires selection of a number of fields. Here we have three values to be taken to cloud (X, Y and Z directions).For display purposes a mobile is used in conjunction with MIT App Inventor. Acceleration record files can be obtained that may be processed further. The application contains three buttons forward, side and vertical which displays the acceleration values across X, Y and Z directions respectively. The acceleration values are further integrated to obtain velocity and displacement .It can be done through 2 ways like ana- log integration and digital integration. But the analog integration is reliable only to measure the sinusoidal steady state values. So the digital integration is much better for obtaining a displacement signal from acceleration. It is possible to use these components for further processing and applications like ultrasonic applications, military devices namely mixers, elevators, mechanically handling equipmentâ€Ÿs and information handling devices like iPad, phones etc.Â Â